2023
DOI: 10.1007/s00432-023-04636-y
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of recurrence and overall survival in esophagogastric cancer after perioperative FLOT and clinical outcomes in MSI-H population: the PROSECCO Study

Abstract: Background FLOT regimen is the standard perioperative treatment in Western countries for patients with locally advanced gastric (GC) or gastroesophageal junction cancer (GEJC). High microsatellite instability (MSI-H) and Mismatch Repair deficient (dMMR) demonstrated a favorable prognostic role and a concomitant negative predictive impact on the benefit of perioperative 5-fluorouracil-based doublets; however, its role in pts receiving FLOT chemotherapy is still unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Similar to our results, an Italian group demonstrated that MSI-H was a positive prognostic marker in perioperatively FLOT-treated patients (Giommoni et al 2021). In addition, in the multicenter, retrospective PRO-SECCO study, the outcome of patients with MSI-H was remarkably better than that of patients with MSS after treatment according to the FLOT protocol (Nappo et al 2023). Furthermore, preliminary results of the DANTE study analyzing FLOT in comparison with FLOT and atezolizumab showed high rates of pathological tumor regression in MSI patients, with the current restriction that survival data are not yet available, and translation of pathological complete response into improved survival of the patients has to be shown (Al-Batran et al 2022).…”
Section: Discussionmentioning
confidence: 97%
“…Similar to our results, an Italian group demonstrated that MSI-H was a positive prognostic marker in perioperatively FLOT-treated patients (Giommoni et al 2021). In addition, in the multicenter, retrospective PRO-SECCO study, the outcome of patients with MSI-H was remarkably better than that of patients with MSS after treatment according to the FLOT protocol (Nappo et al 2023). Furthermore, preliminary results of the DANTE study analyzing FLOT in comparison with FLOT and atezolizumab showed high rates of pathological tumor regression in MSI patients, with the current restriction that survival data are not yet available, and translation of pathological complete response into improved survival of the patients has to be shown (Al-Batran et al 2022).…”
Section: Discussionmentioning
confidence: 97%
“…The FLOT or FOLFOX scheme is currently the recommended first-line therapy to improve the OS in cases of locally advanced HER2-negative CA ( 6 , 15 ). In addition, high microsatellite instability (MSI-H) and Mismatch Repair deficient (dMMR) tumors appear to be favorable prognostic factors ( 16 ), both in terms of nodal status and downstaging ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individual patient data meta-analysis focused on the value of MSI-H as a biomarker in gastric cancer, not using taxanes, and did not show a benefit of perioperative chemotherapy for patients with MSI-H gastric cancer [ 9 ]. On the contrary, the PROSECCO study based on real-world data suggests that the perioperative FLOT regimen is effective in both MSI-H and microsatellite stability (MSS) localized gastric adenocarcinoma being progression-free and overall survival longer in the MSI-H subgroup [ 10 ].…”
Section: Discussionmentioning
confidence: 99%